Food safety knowledge and practice and its relationship with literacy: The case of rural women in Iran - Abedi Sarvestani, Ahmad; Avarand, Amaneh (Social Determinants of Health, 2020)
Background: It is widely understood that most food-borne illness is associated with the inner home environment, and that therefore, the role of women in providing, storage and preparation of healthy food is very important. Given the lack of research on home food safety in Iran, this study focused on the knowledge and behavior towards food safety and its relationship with literacy among rural women. Methods: Data of this cross-sectional survey were collected through questionnaires. The validity of the questionnaire was evaluated by referring to university experts. The questionnaire reliability was evaluated by Cronbach's test (a=0.782). The study population consisted of rural women in the areas of Gonbad-e Kavous County in Golestan province, north of Iran. Using random cluster sampling, 385 women from 77 villages were studied. Descriptive statistics and t-test were used for analysis. Results: Knowledge and behavior of the studied rural women towards food safety could be assessed as good and fair respectively. There was no difference between literate and illiterate women in regard to food safety knowledge (t=1.72; P>0.05), but literate compared with illiterate rural women have in general better food safety behavior (t=2.16; P<0.05). Conclusion: The findings showed that literacy education can activate mechanisms that lead to food safety behavioral changes. However, there was no difference between literate and illiterate women in regard to food safety knowledge. It suggests that illiterate rural women, despite their inability to read and write, can find appropriate methods to learn about food safety issues.